Study of medicine prescribing for elderly patients. Issue 6475 (13th April 1985) - Freer, C B
Abstract : An analysis of drug prescribing over six months in a random sample of 146 elderly patients showed that 42% were receiving one or more medicines long term. Diuretics, analgesics, and non-steroidal anti-inflammatory drugs were most often prescribed, and variations in prescribing by age, sex, and consultations with the general practitioner were examined. Only 17% of the group were taking three or more medicines on repeat prescriptions, and 42% received no prescriptions during the study. These results have implications for the workload of supervising prescriptions but also underline the need for a balanced view of drug prescribing and medicine taking in elderly people.